High‐throughput nucleoside phosphate monitoring in mammalian cell fed‐batch cultivation using quantitative matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry. Issue 1 (18th September 2014) - Steinhoff, Robert F.; Ivarsson, Marija; Habicher, Tobias; Villiger, Thomas K.; Boertz, Jens; Krismer, Jasmin; Fagerer, Stephan R.; Soos, Miroslav; Morbidelli, Massimo; Pabst, Martin; Zenobi, Renato
Abstract Current methods for monitoring multiple intracellular metabolite levels in parallel are limited in sample throughput capabilities and analyte selectivity. This article presents a novel high‐throughput method based on matrix‐assisted laser desorption/ionization (MALDI) time‐of‐flight mass spectrometry (TOF‐MS) for monitoring intracellular metabolite levels in fed‐batch processes. The MALDI‐TOF‐MS method presented here is based on a new microarray sample target and allows the detection of nucleoside phosphates and various other metabolites using stable isotope labeled internal standards. With short sample preparation steps and thus high sample throughput capabilities, the method is suitable for monitoring mammalian cell cultures, such as antibody producing hybridoma cell lines in industrial environments. The method is capable of reducing the runtime of standard LC‐UV methods to approximately 1 min per sample (including 10 technical replicates). Its performance is exemplarily demonstrated in an 8‐day monitoring experiment of independently controlled fed‐batches, containing an antibody producing mouse hybridoma cell culture. The monitoring profiles clearly confirmed differences between cultivation conditions. Hypothermia and hyperosmolarity were studied in four bioreactors, where hypothermia was found to have a positive effect on the longevity of the cell culture, whereas hyperosmolarity lead to an arrest of cell proliferation. The results are in good agreement with HPLC‐UV cross validation experiments. Subsequent principal component analysis (PCA) clearly separates the different bioreactor conditions based on the measured mass spectral profiles. This method is not limited to any cell line and can be applied as a process analytical tool in biotechnological processes.